General design algorithm for stray light suppression of a panoramic annular system - Liao, Yiqi; Gao, Shaohua; Bai, Jian; Wang, Kaiwei (Optics express, 2023)
In this work, a universal algorithm for designing a panoramic annular lens (PAL) system free from stray light is proposed. The impact of a given stray light path to the optical system could be estimated without running a full stray light analysis process, which allows designers to eliminate troublesome stray light paths by optimizing lens parameters at an early stage of optical design. A 360° ×(40°-100°) PAL system is designed and implemented to verify the proposed method. Simulation shows that the point source transmittance (PST) decreases by 2 orders of magnitude at a specific field-of-view (FoV) range after optimizing the system. Experimental results show perfect consistency with the simulation predictions, which indicate that two types of stray light are totally eliminated in the demonstrated system. This stray light analysis and suppression method provides a promising approach for the research and development of ultra-wide angle high performance optical systems.